2021
DOI: 10.1139/apnm-2020-0607
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity energy expenditure and fat-free mass: relationship with metabolic syndrome in overweight or obese postmenopausal women

Abstract: Menopause transition is associated with detrimental changes in physical activity, body composition and metabolic profile. Although physical activity energy expenditure (PAEE) is inversely associated with metabolic syndrome (MetS) in individuals at higher risk of CVD, the association is unknown in low-risk individuals. The aim of the study was to investigate the association between PAEE and MetS (prevalence and severity) in inactive overweight or obese postmenopausal women with a low Framingham Risk Score (FRS:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 61 publications
0
6
0
2
Order By: Relevance
“…Moreover, several authors reported that resistance-training exercises help to build and maintain muscle mass, strength, and function, which can decline with age. Strong muscles support joint health, balance, and mobility, reducing the risk of falls and injuries [77].…”
Section: Aging and Physical Activity In Womenmentioning
confidence: 99%
“…Moreover, several authors reported that resistance-training exercises help to build and maintain muscle mass, strength, and function, which can decline with age. Strong muscles support joint health, balance, and mobility, reducing the risk of falls and injuries [77].…”
Section: Aging and Physical Activity In Womenmentioning
confidence: 99%
“…Moreover, several authors reported that resistance training exercises help to build and maintain muscle mass, strength, and function, which can decline with age. Strong muscles support joint health, balance, and mobility, reducing the risk of falls and injuries [93]. Weight Management and Metabolic Changes: Menopause often brings about weight gain, especially around the abdomen.…”
Section: Aging and Physical Activity In Womenmentioning
confidence: 99%
“…Across populations, higher levels of physical activity are associated with greater attenuation of body fat gain and preservation of lean mass across the lifespan [ 110 ]. Indeed, lifestyle activities that include regular physical activity can effectively improve metabolic health and prevent MetS [ 12 , 111 , 112 ]. Evidence shows that sedentary, overweight, and obese postmenopausal women are very responsive to exercise training, so physical activity is a highly beneficial behavioral practice for improving overall health in this population.…”
Section: Exercise Improves Metabolic Health Following the Menopausementioning
confidence: 99%